Selenium and tellurium chemistry from small molecules to biomolecules and materials - Woollins, J. D. (J. Derek); Laitinen, Risto (Springer, 2011)
Our knowledge of the chemistry of selenium and tellurium has seen significant progress in the last few decades. This monograph comprises contributions from leading scientists on the latest research into the synthesis, structure and bonding of novel selenium and tellurium compounds. It provides insight into mechanistic studies of these compounds and describes coordination chemistry involving selenium and tellurium containing ligands. Contributions also describe the theoretical and spectroscopic studies of selenium and tellurium compounds. Additionally, this monograph outlines the applications of selenium and tellurium in biological systems, materials science and as reagents in organic synthesis and shows how these applications have been a fundamental driving force behind the research into the inorganic and organic chemistry these fascinating elements.